(3EYQGH eG jTcd ef GdMOjK GdfHhis - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s ((3CMeO Hf eMeO Hf CMeO Hf EHQGgje Gdbdbjdi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg CeG HYO aEf LeGYI ef WdHI GdMOjK EdJeShG efi Cf Cedi eNJUQGU ai EYQGH eG jTcd ef GdCdaGX GdhGbYI ai GdCMGOjK cJGH GdgeRI ai MOjK GHf CHj cYH GdCfUGQi s
(3BNQgG (B:s
(3MdaJ dgG HGddg Mdag aGLR dfG Ef ef MOjK hdGUGd hbhdgG Edi GdUHM Ci fRd Edi UdGI GdUHM Ci jUdi UdGI GdUHM BNQ GdcJGH fLR HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B46s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B123s
Keywords: (3GdfMhs